Passive Cooling Strategies Towards the Sustainability of Livestock Building- An Overview - Parag Acharya; Amit Sharma; Yashwant Singh; Rajneesh Sirohi (The Indian Veterinary Journal, 2024)
India, being a tropical country, faces a significant challenge in the livestock sector due to heat stress during the summer months. Heat stress in livestock induces various physiological, biochemicals, behavioral, and adaptive changes, leading to severe reproductive and economic losses. Addressing this issue is crucial for sustainable production and economic returns in the livestock industry. The key to mitigating heat stress lies in effective housing management and ensuring a comfortable micro-environment for the animals. While active cooling systems, relying on conventional energy sources, have been traditionally employed, their economic viability and environmental impact raise concerns. As an alternative, passive cooling methods are gaining attention for their potential to enhance sustainability in livestock building designs.